PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS II SDN 004 TEMBILAHAN KOTA KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Yusmawita Yusmawita (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is based on the low reading ability of second grade students of SDN 004 Tembilahan Kota, for thatresearcher apply STAD type cooperative model to improve students' reading ability. This research is aclassroom action research conducted at SDN 004 Tembilahan Kota, the subject of this research is the secondgrade students of SDN 004 Tembilahan Kota with the number of students 30 students. Based on the results ofresearch, obtained data that students' reading ability has improved after applied STAD type cooperativelearning model. In the first cycle the number of students who reach the minimum mastery is 19 students(73.33%) and in the second cycle has increased to 24 students (86.66%). Based on this acquisition, it can beconcluded that the application of STAD type cooperative learning model can improve the reading ability ofsecond grade students SDN 004 Tembilahan Kota Kecamatan Tembilahan.